Writing and Re-Writing History by Destruction: Proceedings of the Annual Minerva Center RIAB Conference, Leipzig, 2018. Research on Israel and Aram in Biblical Times III - Berlejung, Angelika; Maʾir, Aharon; Oshima, Takayoshi (Orientalische Religionen in der Antike, 2022)
Der Kongressband des Minerva-Zentrums »Research on Israel and Aram in Biblical Times« bündelt die Vorträge, die bei der Konferenz des Zentrums in Leipzig 2018 zum Thema des Schreibens und Umschreibens von Geschichte durch gezielte Zerstörungen in der Region Syrien-Palästina-Mesopotamien gehalten wurden. Eine internationale Gruppe von Wissenschaftlern untersuchte das Thema aus einem multiperspektivischen und interdisziplinären Ansatz heraus: Archäologische Studien, Altorientalistik und Bibelwissenschaften konzentrierten sich auf die Zerstörungen antiker Stätten in Israel und Juda im 1. Jahrtausend v. Chr. Die Perspektive der besiegten Israeliten, Jerusalemer und Judäer wird in den Schriften des Alten Testaments und in der nachbiblischen Literatur ausführlich dargestellt und zeigt, dass die Zerstörungen der Vergangenheit ein Kultur- und Identitätsstifter ersten Ranges waren. Die longue durée der Praxis, durch die gezielte Zerstörung des kulturellen Erbes die Vergangenheit neu zu gestalten, um die Gegenwart nach aktuellen Interessen zu gestalten, wird anhand der Praxis des neuassyrischen Reichs bis in die Neuzeit hinein greifbar und am Beispiel der arabisch-muslimischen Eroberung von »Aramäa« sowie der gegenwärtigen türkischen Politik ausgeführt.InhaltsübersichtAngelika Berlejung/Aren Maeir: Introduction I. Re-Writing History by Destruction: The Archaeology of Ancient Israel and Judah Amihai Mazar: Destruction Events: Their Identification, Causes, and Aftermath. Some Test Cases – Assaf Kleiman: Living on the Ruins: The Case of Stratum XII/XI at Hazor – Igor Kreimerman: Sennacherib, Nebuchadnezzar II, and the Residents of Lachish: An Examination of Decision-Making from Conquest to Destruction – Omer Sergi: Rewriting History Through Destruction: The Case of Tel Reḥov and the Hebrew Bible II. Reflections on Destruction and Loss in Prophetic, Poetic, and Post-Biblical Literature Bob Becking: Echoes in Time: The Perception of Jehoiachin's Amnesty in Past and Present (2 Kings 25:27–30) – David G. Garber: The Trace of Inter-Generational Trauma in the Composition History of Ezekiel – Friedhelm Hartenstein: The End of Judah and the Persistence of Cosmic Order: Understanding History in the Light of Creation in Psalms and Prophetic Books – Yigal Levin: Persian-Period Jerusalem in the Shadow of Destruction – Hillel Mali: From Ritual to the Story of Ritual: The Influence of the Destruction of the Temple on Ritual Writing of the First Century CE III. Circumnavigating History: Isaiah's Response to the Temple Destruction J. Todd Hibbard: Does Isaiah Implicate the Temple in His Pronouncements of Judgment Against Jerusalem? – Lena-Sofia Tiemeyer: Continuity of Worship: The Portrayal of the Temple and Its Cult in Isaiah 40–55 – Clemens Schneider: Destruction and Desert Transformation in Isaiah 43:14–21 – Nathan Macdonald: The Terminology of the Cult in Isaiah 56–66 – Judith Gärtner: »The Dwelling Place of Your Holiness« (Isa 63:15): On the Meaning of Temple Theology in Trito-Isaiah IV. Re-Writing History by Destruction in Assyria Natalie N. May: The Destruction of the Assyrian Capitals – Hanspeter Schaudig: »Uprooting«: A Visual Element of Assyrian Imperialistic Propaganda V. Re-Writing History by Destruction of Heritage Witold Witakowski: The Arameans/Syriacs During the First Three Centuries of the Muslim Rule – Tessa Hofmann: The Treatment of Christian Denominations in the Republic of Turkey